Mutations in TET2 and DNMT3A genes are associated with changes in global and gene-specific methylation in acute myeloid leukemia - Alberto Ponciano-Gómez; Adolfo Martínez-Tovar; Jorge Vela-Ojeda; Irma Olarte-Carrillo; Federico Centeno-Cruz; Efraín Garrido (Tumor Biology, 2017)
Acute myeloid leukemia is characterized by its high biological and clinical heterogeneity, which represents an important barrier for a precise disease classification and accurate therapy. While epigenetic aberrations play a pivotal role in acute myeloid leukemia pathophysiology, molecular signatures such as change in the DNA methylation patterns and genetic mutations in enzymes needed to the methylation process can also be helpful for classifying acute myeloid leukemia. Our study aims to unveil the relevance of DNMT3A and TET2 genes in global and specific methylation patterns in acute myeloid leukemia. Peripheral blood samples from 110 untreated patients with acute myeloid leukemia and 15 healthy control individuals were collected. Global 5-methylcytosine and 5-hydroxymethylcytosine in genomic DNA from peripheral blood leukocytes were measured by using the MethylFlashTM Quantification kits. DNMT3A and TET2 expression levels were evaluated by real-time quantitative polymerase chain reaction. The R882A hotspot of DNMT3A and exons 6–10 of TET2 were amplified by polymerase chain reaction and sequenced using the Sanger method. Methylation patterns of 16 gene promoters were evaluated by pyrosequencing after treating DNA with sodium bisulfite, and their transcriptional products were measured by real-time quantitative polymerase chain reaction.Here, we demonstrate altered levels of 5-methylcytosine and 5-hydroxymethylcytosine and highly variable transcript levels of DNMT3A and TET2 in peripheral blood leukocytes from acute myeloid leukemia patients. We found a mutation prevalence of 2.7% for DNMT3A and 11.8% for TET2 in the Mexican population with this disease. The average overall survival of acute myeloid leukemia patients with DNMT3A mutations was only 4 months. In addition, we showed that mutations in DNMT3A and TET2 may cause irregular DNA methylation patterns and transcriptional expression levels in 16 genes known to be involved in acute myeloid leukemia pathogenesis. Our findings suggest that alterations in DNMT3A and TET2 may be associated with acute myeloid leukemia prognosis. Furthermore, alterations in these enzymes affect normal methylation patterns in acute myeloid leukemia– specific genes, which in turn, may influence patient survival.